Growth performance of hevea clones in sub-tropical Meghalaya - Reju M J; Deka H K; Thapliyal A P; Varghese Y A (Journal of Plantation Crops, 2001)
Effect of seasonal changes on the growth performance of various Heva clones were studied in the sub-tropical climate of Meghalaya in two clonal evaluation trials. Maximum growth and biomass production were recorded during monsoon follwed by post momsoon season, while lowest growth and biomass production were observed during winter. The highest growth and biomass production during monsoon may be attributed to favourable climatic conditions prevailing in the region during the season and low growth during winter may be ascribed to adverse environmental factors which severely retarded the growth and prolonged the immaturity period. Statistically, growth pattern showed significant positive correlation with rainfall, maximum and minimum air temperatures, soil temperature and relatibe humidity, while a negative correlation was observed with sunshine hours and wind velocity. Based on the growth performance, the clones PB 235, RRIM 600 and RRII 203 are performing better from the 1985 clonal trial while RRIC 105, PB 311, RRII 208 and RRII 118 registered the highest growth from the 1986 clonal trial.
Keywords: Biomass; Clones; Growth; Hevea brasiliensis; Seasons; Sub-tropical climate